Integrating Local Wisdom-Based Learning To Preparing The Pancasila Students’ Profile, Yes or No? - Hanandita Veda Saphira (Indonesia Emerging Literacy Education, 2022)
The integration of local wisdom in the field of education has become a hot topic in Indonesia. Hence, there is an opportunity for the implementation of local wisdom in learning. This research is a type of qualitative research with data collection techniques using the library research method. This study aimed to find the implementation of local wisdom in learning through a literature review. The results findings show that there are some benefits of integrating local wisdom based in School, especially to equip the elements of profile Pancasila characteristic in classes. The chance of using local wisdom based in school is also still wide open due to much research on the exploration of local wisdom still not being conducted in class yet, and some of them still need improvement and development. Furthermore, the implications of this research tend to convenience further research to do an improvement and development of using local wisdom based on learning context. Some exploration might be can interfere with by any model of learning or approach or methods, to increase students' profile Pancasila.